An Ayurvedic Approach In The Management Of Hidradenitis Suppurativa (Hs) - A Single Case Report - Dr. Rakshith.M.M. ,; Dr. Beena.M.D.,; Dr. Shashikala V,; Dr. Aditya. J.V., (Revista Electronica de Veterinaria, 2024)
Hidradenitis Suppurativa (HS) is a chronic infective and fibrous disease of the skin bearing apocrine sweat glands. Hidradenitis suppurativa is characterized by painful nodules, abscesses, draining dermal tunnels, and scarring with predilection for intertriginous sites, such as the axilla, groin, and breast regions etc. A retrospective analysis of a population based sample reported the prevalence of HS to be 0.1%; gender- based estimates suggest that the average annual incidence is 12.1% per 100,000 among women, more than twice the average annual incidence of men (5.1 per 100,000).(1) The disease tend to become chronic with subcutaneous extension leading to indurations, sinus and fistula having a profound impact on the quality of life. The clinical features of HS can be compared with Naadivrana mentioned in Ayurveda classics. The treatment modalities of Naadivrana includes mainly Shodhana and Ksara Sutra application are adopted in the present case. In modern system of medicine there are no curative (medical) therapies for HS, only symptomatic treatment can be done. This includes adjuvant therapy (e.g., pain management, smoking cessation, weight loss, treatment of super infections, hygiene practises, topical wound dressings) to topical and systemic agents (e.g., antibiotics, anti-inflammatory agents, anti-androgen drugs) and surgical interventions such as excisional surgery and laser surgery.In the present case   Shodhana Chikitsa  along with Ksharasutra prayoga followed by Shamanaushadis were administered in the course of  3 sittings. Patient was completely cured from sign and symptoms of hidradenitis suppurativa. Hence the protocol adopted here is said to be unique drug formulation in the treatment of Hidradenitis Suppurativa.